Discourse About the News of Makan Bergizi Gratis (MBG) Program on Tiktok - Fikri, Miftakhul; Azhar, Dimas Akhsin; Pradana, Yoka (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2025)
This study aims to examine how discourse about the Makan Bergizi Gratis (MBG) program is constructed and received by the public through the TikTok platform. MBG is an Indonesian government initiative to improve children's nutrition, widely disseminated by national media on social media. The research employs a qualitative approach using Norman Fairclough’s critical discourse analysis, which includes three dimensions are textual analysis, discursive practice, and social practice. Data were collected through documentation of TikTok content from official media accounts and public comments related to the MBG issue. The findings indicate that national media narratives on TikTok tend to be optimistic and constructive in presenting the MBG program’s success, while public comments reflect disappointment, inequality in distribution, and criticism of the program's implementation. This study concludes that TikTok is not merely an information platform but also a contested arena where governmental narratives are challenged by public voices, showing how social media plays a vital role in shaping public opinion and social legitimacy of public policies.